Evaluasi Tempat Penyimpanan Sementara (TPS) Limbah B3 di ORF Porong PT. Pertamina Gas Oeja - Fajar Hidayat; Jawwad, Muhammad Abdus Salam (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
PT Pertamina Gas OEJA, in carrying out its operational and instrument maintenance activities, generates hazardous waste (B3 waste) that must be carefully managed to prevent environmental pollution. This study aims to evaluate the existing condition of the Temporary Storage Facility (TSF) for B3 waste in the context of compliance with applicable regulations. The research method involves collecting data through direct observation of the TSF, followed by comparative analysis with regulations governing B3 waste management. The evaluation results indicate that the TSF is not fully in compliance with the standards of the applicable regulations. Therefore, recommendations for improvement are proposed, including increasing the capacity of waste storage, using more suitable packaging, adjusting the arrangement of packaging/containers to comply with regulations, improving the TSF's roof, and adding completeness to labels and symbols. The implementation of these recommendations is expected to assist Pertagas OEJA in achieving a higher level of compliance with B3 waste management standards and reducing negative environmental impacts.